Inhibition of TREM1 attenuates myocardial ischemia-reperfusion injury-induced cardiomyocyte pyroptosis by suppressing the activation of the NF-κB signaling pathway - Xiaohui Xu; Liang Cai; Xuan Dang; Jianbin Han; Yan Kou; Chunyan Rong; Junjie Kou (PLoS ONE, 2026)
Background Triggering receptor expressed on myeloid cells-1 (TREM-1) is a potent amplifier of inflammatory responses and plays a critical role in the pathogenesis of various infectious diseases. Notably, emerging evidence suggests that TREM-1 is also involved in the development and progression of cardiovascular diseases, such as atherosclerosis and atrial fibrillation. However, its role in myocardial ischemia/reperfusion (I/R) injury remains unclear. This study aimed to investigate the role of TREM-1 in myocardial I/R injury and to explore the potential underlying molecular mechanisms. Methods A hypoxia/reoxygenation (H/R) model was established using HL-1 cardiomyocytes subjected to 6 hours of hypoxia followed by 6 hours of reoxygenation. Pyroptosis levels were assessed by Hoechst-PI staining, lactate dehydrogenase (LDH) release assay, CCK-8 assay, and Western blot analysis. In vivo, a myocardial I/R injury model was established in C57BL/6 mice by subjecting them to 30 minutes of ischemia followed by 24 hours or 7 days of reperfusion. Evaluation was performed using TTC staining, Western blotting, echocardiography, histochemical staining, and immunohistochemistry. Results In this study, we found that TREM-1 expression was significantly upregulated in both in vitro and in vivo models of myocardial ischemia-reperfusion injury (MIRI). Pharmacological inhibition of TREM-1 by LR12 effectively reduced the levels of cardiomyocyte pyroptosis and suppressed activation of the NF-κB signaling pathway. In addition, LR12 treatment alleviated myocardial inflammation and fibrosis and improved left ventricular function in mice.Intervention experiments with MCC950, a specific NLRP3 inhibitor, confirmed that NLRP3 inhibition could mimic the anti-pyroptotic effect of LR12 and reduce the expression of pyroptosis-related proteins. Immunofluorescence experiments further verified that inhibition of NF-κB decreased NLRP3 expression, clarifying the association between TREM-1 downstream signals and NLRP3. Long-term follow-up experiments showed that LR12 treatment significantly reduced the area of myocardial fibrosis at 7 days after reperfusion. Conclusion Our findings indicate that inhibition of TREM-1 alleviates cardiomyocyte pyroptosis during MIRI by suppressing activation of the NF-κB signaling pathway. Therefore, TREM-1 may represent a promising therapeutic target for the treatment of myocardial ischemia-reperfusion injury.